Peranan Penyusunan Anggaran Biaya Produksi dalam Menunjang Efektivitas Pengendalian Biaya Produksi pada PT Elco Indonesia Sejahtera Garut - Cecep Hamzah (Jurnal Wacana Ekonomi, 2017)
This study entitled: "The Role of Production Cost Budgeting in Supporting the Effectiveness of Production Cost Control at PT. Elco Indonesia Sejahtera Garut ”. The purpose of this study was to determine the role of production cost budgeting in supporting the effectiveness of controlling production costs at PT. Elco Indonesia Prosperous Garut. The method used in this research is descriptive analysis method. Data analysis and hypothesis testing used is qualitative analysis, and the data source is secondary data. Based on the results of research and discussion, it can be concluded that the effectiveness of controlling production costs at PT. Elco Indonesia Sejahtera Garut has been achieved because the difference in budget and realization of production costs does not exceed the tolerance limit in general, namely 10%.